Computational insight into the antagonistic activity of some natural ligands against protease-activated receptors in psoriasis - Anurag Agrawal; Vipin Bhati
Psoriasis is a unique skin dermatoses characterised by autoimmune and inflammatory features in humans. Along with these features, pain and itching are the cardinal signs of psoriasis. Lately, many researchers investigated the implications ofprotease-activated receptors, especially PAR-1 and PAR-2, in skin diseases such as psoriasis. In the current study, molecular docking was carried out with AutoDock tools v 1.5.6 to find out binding interactions of some natural ligands, with PAR-1 and PAR-2, which have been preclinically evaluated as antipsoriatic agents, but their mechanism of action has not been established. For this purpose, three-dimensional structures of plant ligands were prepared using the ChemSketch 2015 free version and interactions were observed via Biovia Discovery studio version 4.5. This study demonstrated that Capsaicin and Dimethyl Fumarate, in terms of binding interactions, could behave as protease-activated receptor-1 and protease-activated receptor-2 selective antagonists, respectively. Moreover, molecular dynamic simulation was also performed employing the Desmond module (Schrodinger, LLC, Cambridge, USA) to examine the stability of the ligand-target complex at 100 ns.